Nanoporous Double-Gyroid Structure from ABC Triblock Terpolymer Thick Films - Karim Aissou; Maximilien Coronas; Daniel Hermida-Merino; Eduardo Solano; Didier Cot; Stéphanie Roualdes; Denis Bouyer; Damien Quemener (International Journal of Polymer Science)
The creation of nanostructured materials with a triply periodic minimal surface (TPMS), defined as a zero mean curvature surface having periodicity in three-dimensional space, is an emerging solution to optimize transport (i.e., the ion-conductivity and hydraulic permeability) through the next-generation of electrolyte and ultrafiltration (UF) membranes. Here, we used an amphiphilic ABC-type block copolymer (BCP) (namely, polystyrene-block-poly(2-vinylpyridine)-block-poly(ethylene oxide) (PS-b-P2VP-b-PEO)) to generate symmetric thick films (~8 μm) composed entirely of a TPMS-based structure, consisting of a PS matrix with a double gyroid (DG) minimal surface and hydrophilic stimuli-responsive (P2VP/PEO) nanochannels. To produce the core/shell DG-structured monoliths, we used a process combining the nonsolvent-induced phase separation (NIPS) process with a solvent vapor annealing (SVA) treatment. From such symmetric ABC-type BCP-thick films generated by NIPS-SVA, a mean hydraulic permeability as high as 514 L h-1 m-2 bar-1 was measured. This mean value was revealed to be nearly equal to that of asymmetric PS-b-P2VP-b-PEO membranes manufactured by NIPS, which have a substructure with an implicit irregular and random distribution of the internal pore structure and a skin layer with P2VP/PEO nanopores arranged into a hexagonal array.